Penggunaan Metode Contextual Teaching And Learning Untuk Meningkatkan Hasil Belajar Siswa Madrasah Ibtidaiyah - Moh. Nasrul Amin (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2018)
The purpose of this study is to improve student learning outcomes on the theme Thematic Theme 6 Caring for Animals and Plants Subtema 1 Caring for Animals around Class II MI Ishlahul Masalik Solokuro Lamongan Lesson 2017-2018. The type of research data used in this study is the type of data Qualitative and Quantitative research. The location in this research is MI Ishlahul Masalik Tebluru Solokuro Lamongan. The subject of this research is class II MI Ishlahul Masalik Tebluru Solokuro Lamongan Lesson Year 2017-2018 which amounted to 20 students. Techniques used in data collection is by interview techniques, observation, documentation, and tests. Based on the analysis and discussion, it can be concluded that the use of Contextual Teaching And Learning method can improve student learning outcomes of thematic subjects in MI Ishlahul Masalik Tebluru Solokuro Lamongan Lesson Year 2017-2018. This can be proved by the increase in learning outcomes for each cycle. In cycle I, the average score of student learning test result is 66,00 with percentage 50%. It is known by comparing between pre cycle value and Cycle I value, test result where cycle value I is greater than pre cycle from mean value, that is: 57,75,00> 25,25. While in cycle II, the average value of the test is 73.50 with a percentage of 75%. It is known by comparing the value of cycle I with Cycle II value, the test result where the value of cycle II is greater than the cycle I of the average value, namely: 73.50> 66.00. And in cycle III, it can be seen that the average value of the test result is 81.00 with the percentage of 85%. It is known by comparing the value of cycle II with the value of Cycle III, the test results where the value of cycle III is greater than the cycle II of the average value, namely: 81.00> 73.50. Based on the results of the study, it can be concluded that the use of make a match method can improve students' learning outcomes Thematic Theme Theory 6 Caring for Animals and Plants Subtema 1 Animals in Second Class II MI Ishlahul Masalik Tebluru Solokuro Lamongan Lesson 2017-2018.